Safety, Immunogenicity, and Efficacy of Cytomegalovirus Vaccines: A Systematic Review of Randomized Controlled Trials - Manuela Chiavarini; Anita Genga; Giorgia Maria Ricciotti; Marcello Mario D’Errico; Pamela Barbadoro (Vaccines)
Background/Objectives: Cytomegalovirus (CMV) is widespread and mostly causes asymptomatic infections in immunocompetent hosts, but it may lead to severe and life-threatening diseases in immunocompromised individuals, such as transplant patients and congenitally infected children, representing a significant public health concern. Although there are no licensed CMV vaccines, the development of a CMV vaccine is considered a high priority due to its potential to reduce the burden associated with CMV-related complications, and several approaches are under investigation. The objective of this systematic review was to synthesize the evidence on various CMV vaccines currently under clinical development. Methods: According to the PRISMA guidelines (PROSPERO ID: CRD42024516601), a comprehensive literature search was conducted to identify all the randomized controlled trials that have evaluated the safety, immunogenicity, and efficacy of vaccine candidates compared to a placebo. A total of 26 studies were identified: 11 on transplant patients and 15 on healthy individuals. Results: Several vaccine candidates have shown encouraging results in terms of safety and specific immune responses, notably adjuvanted gB vaccines and DNA vaccines targeting gB and pp65. The results were divided into RCTs on healthy individuals and those on transplant recipients, because the CMV-specific immune response to a vaccine is complex and varies depending not only on the type of vaccine, but also on the immunological status of the individual. Conclusions: Challenges remain in achieving broad efficacy across diverse populations, particularly for immunocompromised patients. Thus, the present work seeks to support future decisions and guide further research in the development of an effective and widely available CMV vaccine.